Proteomic Analysis of the Intestinal Resistance to Thyroid Hormone Mouse Model With Thyroid Hormone Receptor Alpha Mutations - Xi, Yue; Zhang, Dan; Liang, Yue; Shan, Zhongyan; Teng, Xiaochun; Teng, Weiping (Frontiers in Endocrinology, 2022)
Thyroid hormone (TH) is critical during the development of vertebrates and affects the function of many organs and tissues, especially the intestine. Triiodothyronine (T3) is the active form and can bind to thyroid hormone nuclear receptors (TRs) to play a vital role in the development of vertebrates. Resistance to thyroid hormone α (RTHα) seen in patients has been mimicked by the Thra E403X mutation. To investigate the mechanisms underlying the effect of TRα1 on intestinal development, the present study employed proteomic analysis to identify differentially expressed proteins (DEPs) in the distal ileum between homozygous ThraE403X/E403X and wildtype Thra+/+ mice. A total of 1189 DEPs were identified, including 603 upregulated and 586 downregulated proteins. Proteomic analysis revealed that the DEPs were highly enriched in the metabolic process, the developmental process, the transporter of the nutrients, and the intestinal immune system related pathway. Of these DEPs, 20 proteins were validated by parallel reaction monitoring analysis. Our intestinal proteomic results provide promising candidates for future studies as they suggest novel mechanisms by which TRα1 may influence intestinal development, such as the transport of intestinal nutrients and the establishment of innate and adaptive immune barriers of the intestine.